2006
DOI: 10.1103/physrevlett.96.083901
|View full text |Cite
|
Sign up to set email alerts
|

Conclusive Evidence of an Attosecond Pulse Train Observed with the Mode-Resolved Autocorrelation Technique

Abstract: We report on the direct observation of an attosecond pulse train with a mode-resolved autocorrelation technique. The chirp among the three harmonic fields is specified by analyzing two-photon above-threshold ionization spectra of electrons, resulting in a pulse duration that should be shorter than 450 as, which is, to our knowledge, the first determination of the chirp in the attosecond pulse train with an autocorrelation technique. These results will open the way to full characterization of an attosecond puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
79
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 22 publications
0
79
1
Order By: Relevance
“…To address the question of mutual coherence among XUV harmonics and the resulting attosecond pulse generation from overdense plasmas, we have chosen the method of XUV autocorrelation (AC), which has already been applied successfully to the temporal characterization of atomic harmonic emission [24][25][26] (for details, see the Methods section). The technique is demanding in itself, but its application to plasma harmonics presents a particularly formidable challenge.…”
mentioning
confidence: 99%
“…To address the question of mutual coherence among XUV harmonics and the resulting attosecond pulse generation from overdense plasmas, we have chosen the method of XUV autocorrelation (AC), which has already been applied successfully to the temporal characterization of atomic harmonic emission [24][25][26] (for details, see the Methods section). The technique is demanding in itself, but its application to plasma harmonics presents a particularly formidable challenge.…”
mentioning
confidence: 99%
“…So far, the direct measurement of the spatiotemporally averaged duration of the individual pulses of an as-pulse train was based on the second-order AC technique [24,32]. An extension of the technique to a frequency-resolved optical gating (FROG)-like approach will provide detailed information, i.e.…”
Section: Toward Xuv-frog-type Measurementsmentioning
confidence: 99%
“…Instead, this is achieved by triggering two-photon ionization processes with the XUV radiation and subsequent detection of the generated ions or PEs. Several materials and different ionization processes have been investigated in this context such as two-photon ionization of helium [29,30], two-photon above-threshold ionization (ATI) of helium [31][32][33], two-photon double ionization of helium [34] and two-photon ATI of argon [33,35]. In all cases, the ions or PEs were detected using suitable ion or electron time-of-flight (TOF) spectrometers.…”
mentioning
confidence: 99%
“…Experimental efforts in this time scale have been restricted to XUV-IR pump-probe schemes [1][2][3][4][5][6][7] or in situ electron-ion collision methods [8]. Systematic developments in highpulse-energy HHG [9][10][11][12][13] and XUV supercontinua [14][15][16][17][18][19] paved the way to time-delay spectroscopic studies [20] and XUV-pump-XUV-probe experiments [21,22] that have lately demonstrated their first proof-of-principle application in the measurement of induced, ultrafast evolving atomic coherences in an atomic continuum [20,22]. Such measurements are free of interventions from unwanted channels, opened through quasiresonant multi-IR-photon transitions.…”
Section: Introductionmentioning
confidence: 99%